Association of Periodic Limb Movements With Medication Classes: A Retrospective Cohort Study. (12th April 2022) - Hoxha, Ortenc; Jairam, Trevor; Kendzerska, Tetyana; Rajendram, Phavalan; Zhou, Ryan; Ravindran, Prashanthan; Osman, Sinan; Banayoty, Monica; Qian, YuChen; Murray, Brian J.; Boulos, Mark I.
Abstract : Background and Objectives: To investigate the association between various medication classes and the periodic limb movement index (PLMI) in a clinical cohort of adults who completed in-laboratory polysomnography. Methods: A single, diagnostic, overnight, in-laboratory polysomnogram was completed for 3, 488 patients consecutively referred from 2010 to 2015 to determine PLMI. Medication use and medical comorbidities were collected through patient questionnaires. Associations between medication classes and PLMI were ascertained using multivariable ordinal logistic regression models. Results: The median age of the cohort was 56.0 years (48.2% male). After adjusting for age, sex, body mass index, relevant comorbidities, and sleep measures, the use of selective serotonin reuptake inhibitors (SSRIs) (odds ratio [OR] 1.52) and serotonin-norepinephrine reuptake inhibitors (SNRIs) (OR 1.99) was associated with increased PLMI. Conversely, gabapentinoids (OR 0.71), stimulants (OR 0.52), benzodiazepines (OR 0.79), and dopamine agonists (OR 0.38) were associated with decreased PLMI. A non–statistically significant trend for decreased PLMI with neuroleptic use was observed. No significant associations were found between PLMI and the use of antihypertensives, statins, tricyclic antidepressants, bupropion, anticoagulants, antiplatelets, modafinil, and antihistamines. Discussion: The use of SSRIs and SNRIs was associated with elevated PLMI while the use of gabapentinoids, stimulants, benzodiazepines, and dopamine agonists was associated with decreased PLMI. These results can assist physicians in managing periodic limb movements in sleep (PLMS) and invite further research into the relationship between PLMS and medications with the modulating effects of dose, formulation type, and time of administration. Classification of Evidence: This study provides Class II evidence that SSRIs and SNRIs are associated with elevated PLMI while gabapentinoids, stimulants, benzodiazepines, and dopamine agonists are associated with decreased PLMI.